Nursing care of the pediatric neurosurgery patient - Cartwright, Cathy C.; Wallace, Donna C. (Springer, 2017)
This book offers a detailed reference for nurses, explaining pathophysiology, anatomy, radiodiagnostic testing and treatment options for each neurosurgical diagnosis. Includes case studies, impact on families, patient and family education, and practice pearls.